MODERN CHALLENGES AND NEWEST ASYMMETRIES OF THE FISCAL SPACE OF THE STATE - Sidelnykova , L. P. (The actual problems of regional economy development, 2024)
The article is focused on researching the interaction of tax, budgetary and debt aspects of the formation of the fiscal space of Ukraine under martial law. It is proved that the imbalance of the public finance system in 2022-2024 contains critical threats to ensuring macroeconomic equilibrium and a positive trajectory of social development. It is established that the full-scale invasion of the russian federation had an extremely negative impact on the generation of tax sources for the formation of budget resources, and the budget revenues generated by the domestic economy are sorely lacking to ensure timely and complete performance of the state functions. It is determined that in such circumstances, Ukraine is forced to borrow actively. Moreover, domestic sources of financing the budget deficit in the conditions of hostilities are quite limited, so the emphasis is on external government borrowing The purpose of the article is to identify the newest asymmetries of the fiscal space of the state, which are intensively generated in conditions of uncertainty during the war, and to develop proposals for their balance. The specifics of the scientific tasks, which are the subject of the research, required the use of a set of special methods, the application of which helped to identify current trends in the formation and use of funds of the State Budget of Ukraine, which produce a rapid accumulation of external public debt. It is established that Ukraine uses its own state budget revenues almost exclusively to finance defense, while other functions of the state are paid for by foreign aid. At the same time, the current trend in the structure of foreign aid to Ukraine, which is gradually refocusing on the format of loans, is recorded. As a result of the research, it is proved that the main way to improve the situation is to recover the national economy and fight against corruption and the shadow sector, which significantly reduce the amount of tax revenues to the state budget. Reducing the state debt will be possible, firstly, through fiscal reforms that will increase the efficiency of tax and fee mobilization; secondly, through the use of fiscal space that will result from the broadening of the tax base for productive expenditures.